New perspectives in Indian literature in English : essays in honour of professor M.K. Naik (Sterling Publishers, 1995)
This is a collection of essays and studies by eminent scholars from India and abroad on some important aspect of Indian literature in English. The scope of this book is so wide as to include essays in general on the meaning and appeal of India-- its mysticism, mythology, aesthetics and poetics, and special studies of the poetic works of Sri Aurobindo, Tagore, Parthasarathiy, Ramanujan, Daruwalla and Kolatkar; the novels of Raja Rao, Mulk raj anand and Arun joshi; and the autobiographies of gandhi, Nehru and Chaudari, as also an appraisal of Muslim writers in English